Video analysis of Achilles tendon rupture in male professional football (soccer) players: injury mechanisms, patterns and biomechanics. Issue 3 (22nd September 2022) - Della Villa, Francesco; Buckthorpe, Matthew; Tosarelli, Fillippo; Zago, Matteo; Zaffagnini, Stefano; Grassi, Alberto
Abstract : Background: Achilles tendon rupture (ATR), while rare in football, is a severe career-threatening injury associated with long-layoff times. To date, no study has documented ATR's mechanism in professional football players. Aim: To describe the mechanisms, situational patterns and gross biomechanics (kinematics) of ATR injuries in professional male football players. Methods: Eighty-six (n=86) consecutive ATR injuries in professional football players during official matches were identified. Sixty (70%) injury videos were identified for mechanism and situational pattern, with biomechanical analysis feasible in 42 cases. Three independent reviewers evaluated the injury videos. Distribution of ATR during the season, the match play and on the field were also reported. Results: Fifty (n=50, 83%) injuries were classified as non-contact and 10 (17%) as indirect contact. ATRs are injuries occurring during accelerations; three main situational patterns were identified: (1) forward acceleration from standing (n=25, 42%); (2) cross-over cutting (n=15, 25%) and (3) vertical jumping (n=11, 18%). Biomechanically, ATR injuries were consistent with a multiplanar loading at the injury frame consisting of a slightly flexed trunk (15.5°), extended hip (−19.5°), early flexed knee (22.5°) and end-range dorsiflexed (40°) ankle in the sagittal plane and foot pronation; 27 (45%) ATRs occurred in the first 30 min of effective match time. Conclusions: All ATRs in professional football were either non-contact (83%) or indirect contact (17%) injuries. The most common situational patterns were forward acceleration from standing, cross-over cutting and vertical jumping. Biomechanics was consistent and probably triggered by a multiplanar, although predominantly sagittal, loading of the injured Achilles tendon.